Emotional learning for developing emotional skills in children and adolescents - Pérez, Núria; Filella, Gemma (Universidad Pedagógica y Tecnológica de Colombia, 2019)
On the basis of the conviction that education must prepare people for life, during the last years a movement for promotion, dissemination, and development of emotional learning as a psycho-pedagogical innovation has been generated. Its starting point is curricula in all stages with a life cycle approach. This article provides guidelines for its implementation as well as for program creation in educational centers at any level. A proposal is made regarding the most appropriate curricular content and objectives for the 3-16 age group. The article also reflects on the skills to be developed, the appropriate methodologies or didactical strategies, and the criteria to take into consideration for the creation of emotional learning programs.